QUALITATIVE AND QUANTITATIVE ANALISIS OF ORGANIC ACIDS IN MIXTURE OF MULTIVITAMIN RAW MATERIAL - V. Yu. Zhilkina; A. I. Marakhova; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств)
The article presents the results of a qualitative analysis of organic acids in the mixture of the multivitamin raw material № 2. Thin layer chromatography method was confirmed to contain apple, citric and ascorbic acids. Quantitative analysis of the amount of organic acids and ascorbic acid was conducted by potentiometric titration method developed by the authors. The results were compared with the datas of the indicator titration and coulometry. The advantage of using a potentiometer to more accurately establish the endpoint was showed.